Pharmaceutical orientation and applications of silver/zinc oxide nanoparticles developed from various fruit peel extracts: an emerging sustainable approach - Mahima Chaudhary; Priyvart Choudhary; Anjali Tripathi; Vinay Kumar Pandey; Rohit Sharma; Seema Singh; Sarvesh Rustagi; Amritanshu Pathak (Discover Sustainability)
Abstract Nanotechnology has witnessed a paradigm shift with the emergence of a sustainable and eco-friendly approach for the synthesis of Ag/ZnO nanoparticles utilizing various fruit peel extracts. The inherent bioactive compounds present in fruit peels offer a green alternative, aligning with global efforts toward environmentally responsible nanotechnologies. This approach not only mitigates environmental impacts but also taps into cost-effective and readily available resources for nanoparticle synthesis. The scope of this study encompasses a comprehensive exploration of the substantial utilization and applications of Ag/ZnO nanoparticles derived from diverse fruit peel extracts. This study delves into a green synthesis process, considering a range of fruit sources to optimize nanoparticle characteristics. This approach involves tailoring nanoparticles for specific applications by fine-tuning synthesis parameters, diversifying fruit sources, and fostering interdisciplinary collaborations. The emerging sustainable approach of utilizing Ag/ZnO nanoparticles from various fruit peel extracts represents a transformative shift in nanotechnology. The controlled release of zinc from nanoparticles opens avenues for agricultural applications, enhancing nutrient availability for plants and elevating crop yields. The customization of nanoparticles for catalysis, sensing, and optoelectronics highlights their versatility and adaptability for diverse industrial applications. This eco-friendly methodology, grounded in green synthesis principles, has diverse applications with far-reaching implications. Embracing this transformative pathway ensures not only the optimization of nanoparticles for specific applications, but also a more sustainable and ethical trajectory for nanotechnology, contributing to the well-being of both industries and the environment.